The Growing Gap Between Emerging Technologies and Legal-Ethical Oversight
XXXII, 212 p.
Keywords: At the same time that the pace of science and technology has greatly accelerated in recent decades, our legal and ethical oversight mechanisms have become bogged down and slower. This book addresses the growing gap between the pace of science and technology and the lagging responsiveness of legal and ethical oversight society relies on to govern emerging technologies. Whether it be biotechnology, genetic testing, nanotechnology, synthetic biology, computer privacy, autonomous robotics, or any of the other many emerging technologies, new approaches are needed to ensure appropriate and timely regulatory responses. This book documents the problem and offers a toolbox of potential regulatory and governance approaches that might be used to ensure more responsive oversight.